Development of sweet potato (Ipomoea batatas Lamk.) as excipient in tablet formulation - Lamia Diang Mahalia; Stefanus Supriyanto; Yandi Syukri (SAGE Publishing, 2020)
Background: Sweet potato has a potential to be used as a raw material for tablets. However, it needs chemical modifications to produce derivatives with excellent pharmaceutical characteristics. The primary purpose of this research was to use sweet potato starch (Ipomoea batatas Lamk.) as a tablet excipient modified through a chemical process. Design and Methods: This study is experimental and is divided into three stages. The first stage is the extraction process to obtain sweet potato starch. The second stage is the chemical modification of sweet potato starch using pentanol-1 and glacial acetic acid. The third step is the analysis of the pharmaceutical properties of the mutated lab model compared to the control sample and Amprotab. Results: The descriptive-comparative analysis showed sweet potato starch modified with panthenol-1 had a higher hardness value (=2.55±0.34) compared to native starch (1.00±0.08). The particle size distribution of the modified sample with acetate acid (=15.20±1.79) was higher than the others. Conclusions: In conclusion, modified sweet potato starch has better pharmaceutical properties than native starch. Further research needs to be conducted on the magnitude of the potential of sweet potato starch as an excipient, both as filler, a binder, and a crushing agent on tablet preparations.